2017
DOI: 10.1177/1687814017720081
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the geometry of impinging surface on the pressure oscillations of self-resonating pulsed waterjet

Abstract: A preliminary experimental investigation was performed with a focus on the axial pressure oscillations of self-resonating pulsed waterjet under different impinging surfaces. Five target plates of different impinging surfaces were impinged by self-resonating pulsed waterjets at various standoff distances and under four inlet pressures. It was found that the geometry of impinging surface significantly affects the pressure oscillation peak and amplitude of self-resonating pulsed waterjet, and the influences large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…Moreover, it should be noticed that this development trend of the pressure oscillation peak and amplitude is a typical feature of SRWJs that had been demonstrated by Johnson et al [15], Chahine et al [17], and Li et al [19]. In addition, the results of our previous research have also confirmed this typical feature of SRWJ [29][30][31]35]. So, that is to say, at an inlet pressure of 10 MPa, only organ-pipe nozzles with a downstream contraction ratio of 2.5 can generate effective SRWJ that has large pressure oscillations.…”
Section: Bd Sensorssupporting
confidence: 87%
See 3 more Smart Citations
“…Moreover, it should be noticed that this development trend of the pressure oscillation peak and amplitude is a typical feature of SRWJs that had been demonstrated by Johnson et al [15], Chahine et al [17], and Li et al [19]. In addition, the results of our previous research have also confirmed this typical feature of SRWJ [29][30][31]35]. So, that is to say, at an inlet pressure of 10 MPa, only organ-pipe nozzles with a downstream contraction ratio of 2.5 can generate effective SRWJ that has large pressure oscillations.…”
Section: Bd Sensorssupporting
confidence: 87%
“…A schematic diagram of the experimental setup for measuring the axial pressures of SRWJs under different values of the downstream contraction ratio is shown in Figure 2. It should be noticed that the experimental method and the main equipment and facilities shown in the figure were all the same with those used in our previous investigations [25][26][27][28][29][30][31][32], except for the organ-pipe nozzles. Therefore, the schematic of the experimental set-up is the same as the previous ones [31,35].…”
Section: Experimental Setup and Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…Most recently, we studied the preferred Strouhal number used in SRWJs, and found that the optimum values are 0.315 and 0.278 respectively, corresponding to inlet pressures of 10 MPa and 20 MPa [20]. Furthermore, a series of experimental investigations on SRWJs have also been conducted, ranging from the effects of nozzle inner surface roughness to the influence of feeding pipe diameter [21][22][23][24][25][26][27][28][29]. These investigations on the mechanisms and principles of SRWJs have contributed to the understanding of the jet and improvement of the jet's performance.…”
Section: Introductionmentioning
confidence: 99%